3(x-2)+3(2x+2)=-3(2-x)

Simple and best practice solution for 3(x-2)+3(2x+2)=-3(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)+3(2x+2)=-3(2-x) equation:


Simplifying
3(x + -2) + 3(2x + 2) = -3(2 + -1x)

Reorder the terms:
3(-2 + x) + 3(2x + 2) = -3(2 + -1x)
(-2 * 3 + x * 3) + 3(2x + 2) = -3(2 + -1x)
(-6 + 3x) + 3(2x + 2) = -3(2 + -1x)

Reorder the terms:
-6 + 3x + 3(2 + 2x) = -3(2 + -1x)
-6 + 3x + (2 * 3 + 2x * 3) = -3(2 + -1x)
-6 + 3x + (6 + 6x) = -3(2 + -1x)

Reorder the terms:
-6 + 6 + 3x + 6x = -3(2 + -1x)

Combine like terms: -6 + 6 = 0
0 + 3x + 6x = -3(2 + -1x)
3x + 6x = -3(2 + -1x)

Combine like terms: 3x + 6x = 9x
9x = -3(2 + -1x)
9x = (2 * -3 + -1x * -3)
9x = (-6 + 3x)

Solving
9x = -6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
9x + -3x = -6 + 3x + -3x

Combine like terms: 9x + -3x = 6x
6x = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
6x = -6 + 0
6x = -6

Divide each side by '6'.
x = -1

Simplifying
x = -1

See similar equations:

| 4p+3=2p+5 | | 5/9y=-35/81 | | 8(y-2)=4y-32 | | A/5+8=5 | | 8x^2-17x+2=0 | | 3x^2+6x+77=0 | | 9x-z(7x-1)=2 | | 3.2x+6.57=-21.91 | | -2*-2.5-4=1.5*-2.5+7 | | Y/9-2=5 | | 5x-7y=16fory | | X-5.5=4.5 | | X+5.2=3 | | 9^2n=1/6561 | | s+2=7 | | 6+20/a-4=5a/a-4 | | 9^2n1/6561 | | m/4=-14 | | X-47=18 | | 5x^2-30x+12=0 | | 5x+x^2=180 | | 110=n^2+n | | (16-y)/4=6 | | 0.50x+0.20y=3.00 | | -3x^2+7x+2=0 | | 288x^3+11187.45x^2-72500=0 | | 5x-9=5x-29 | | 300x-0.62=100x+0.02 | | -3x^2+8x+9=0 | | 6x-10=x+5 | | (x+5+x-2)=54 | | -4x^2+9x+9=0 |

Equations solver categories